Society Values Based On Islamic Education - Talhah Ajmain, Muhammad; Istiqamah Mohamad Zaki, Nurul; Nur Hadis A Rahman, Siti (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
Islam is a comprehensive religion, it contains strong principles and resources such as ‘aqidah, worship, shari‘a, and morals that aim to regulate the life and journey of human beings in this world and the afterlife in the aspects of individual management, household, education, economy, politics, social law, culture, etc. The Al-Quran and al-Sunnah, as well as the great heritage of Islamic scholars, contain all human life guides. The purpose of life and the human role in the world is to 'ubudiyyah (worship) Allah swt. Therefore, every act and movement of people in this world should be focused on the goal of carrying out their duties as khalifatullah, that is, the caliph of God on this earth. This concept paper aims to explore the practice of social life in the time of the Prophet Muhammad, explaining the basic concessions of social life and society based on Islamic education. This article uses the library method and document analysis. This paper will help to provide some sources of information that can be used by people who would like to understand and study the social values based on Islamic education. As a conclusion, Islamic education takes over as the primary educational model and is no longer an option to be selected or rejected. The application of these values as a whole must be mobilized, starting with working on an educational philosophy based on monotheism, the preparation of a teacher education curriculum, and the formation of a student education curriculum. Keywords: Society Values, Islamic Education, Social Life.